1986
DOI: 10.1038/322836a0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of murine gamma genes and expression in fetal and adult T lymphocytes

Abstract: The search for the genes encoding the T-cell receptor alpha and chains revealed a third gene, T gamma (ref. 1), which shares with t T alpha (refs 2-7) and T beta (refs 8-15) genes a number of structure features, including somatic rearrangement during T-cell development. T gamma gene expression appears to be unnecessary in son mature T cells and is at its greatest in fetal thymocytes encouraging speculation that T gamma has a role in T-cell development and may be involved in the recognition of polymorphic major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
297
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(307 citation statements)
references
References 48 publications
10
297
0
Order By: Relevance
“…In addition, however, each hybridoma expressed other y transcripts, which may be nonfunctional . The expression of nonproductive y transcripts in T cells has been frequently observed (12,30,(32)(33)(34) . Taken together, our data suggest that three distinct y chains encoded by Vy2 Jy1Cyl, Vy4Jy1Cy1, and Vy1 .3Jy4Cy4 rearranged genes, are represented among five y/8 T hybridomas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, however, each hybridoma expressed other y transcripts, which may be nonfunctional . The expression of nonproductive y transcripts in T cells has been frequently observed (12,30,(32)(33)(34) . Taken together, our data suggest that three distinct y chains encoded by Vy2 Jy1Cyl, Vy4Jy1Cy1, and Vy1 .3Jy4Cy4 rearranged genes, are represented among five y/8 T hybridomas.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that the potential diversity of the y chain in the mouse is relatively limited, with only seven (known) V gene segments, three functional J segments, and no known D segments (9-13) . While there is clear evidence ofjunctional diversity created at VyJY joints, presumably due in part to the addition of random nucleotides (N regions), the extent of N diversity in y chains may be relatively limited (9)(10)(11)(12) . Moreover, y gene use in the adult thymic population of y/S cells is strikingly nonrandom, with most cells expressing the product of a single rearranged gene, Vy2Jy1Cy1 (34a, 34b) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike αβ T cells, γδ T cells are functionally committed during intra‐thymic differentiation 28, 29. In mice, the TCR‐ γ locus consists of seven V γ (V γ 1–V γ 7) genes (Heilig & Tonegawa's nomenclature30) that are closely correlated with the effector function, although V γ 3 is a pseudogene in most mouse strains 31. Production of IL‐17 is mostly limited to V γ 4 + and V γ 6 + γδ T cells,32 although V γ 1 + γδ T cells also produce IL‐17 in some cases 33.…”
Section: γδ T‐cell Subsets and Their Developmentmentioning
confidence: 99%
“…The y chain gene family is known to encode four C regions (1 pseudogene) and seven V regions which can give rise to at least five y chain mRNA transcripts (8)(9)(10)(11)(12)(13) . It is unknown if all these transcripts give rise to cell surface-expressed proteins.…”
mentioning
confidence: 99%